Mencapai work engagement pada karyawan : Bagaimana peranan psychological well-being dan work life balance? - Ferrysandi, Bryan Nifenty; Nainggolan, Eben Ezer; Ul Haque, Sayidah Aulia (SUKMA : Jurnal Penelitian Psikologi, 2024)
The purpose of this study is to examine whether psychological well-being and work life balance are related to work engagement in employees. The population in this study were employees in Surabaya City. The sample size for this study was 287 people, as determined by the Isaac and Michael table, with an error rate of 10%. The approach used is quantitative correlational, with simple random sampling technique. The measurement tools used were the Scale of Psychological Well-being (SPWB) (18 items), the Work/Nonwork Interference and Enhancement Scale (17 items), and the Utrecht Work Engagement Scale (UWES) (17 items) to measure work engagement. The results of this study include multiple linear regression, t-test, variable means, and effective contribution. The results showed that psychological well-being and work life balance significantly increased work engagement (F = 52.664; r = 0.520; R Square = 0.271; P < 0.000). Psychological well-being and work life balance can be used as techniques for employees to build and improve employees' work engagement with the company and their work